Microbial Quality of Fish in Retail Trade in Cochin - V., Narayanan Nambiar; K., Mahadeva Iyer (Fishery Technology, 2025)
Microbial quality of fresh and frozen fish in retail trade in Cochin is presented. 9.4% of the fresh fish and 4.7 % of the frozen fish samples examined had total plate ounts more than 5.0 x 105 g-1 Escherichia coli was detected in 89.8% of the fresh sh and 86.6 % of the frozen fish, and their numbers were more than 20 g-1 in 78.2 and 1.2% of the samples respectively. Faecal streptococci were detected in all the fresh sh and 87.4 7; of the frozen fish and their numbers were more than 1000g-1 in 60.3 nd ll % of the samples respectively. Salmonella was detected in 5.8 and 8.7% of the fresh and frozen fish samples respectively.